Dental follicles promote soft tissue management in surgical exposure of labially impacted maxillary canine - Li-Ru Hu (BMC, 2021)
Abstract Background The present study aimed to report a technically improved operation on the surgical exposure of labially impacted maxillary canine, elaborating the management of soft tissue to achieve better aesthetic results, and post-treatment periodontal health. Methods Patients sought orthodontic treatment with unilateral labially impacted maxillary canines were selected in this study. The impacted teeth were assigned to the experimental group and contralateral unimpacted canines were assigned to the control group. The impacted canines were surgically exposed with dissected dental follicle (DF) stitching to muscle and mucosa surrounding the crowns. The gingival index (GI), probing depth (PD), the width of the keratinized gingiva (WKG), gingival scars (GS), bone loss (BL), and apical root resorption (ARR) were recorded after the removal of the fixed appliance. A two-sample t-test was used for independent samples for parametric variables. Results A total of 24 patients with unilateral maxillary canine impaction were successfully treated. The outcomes of GI, WKG, GS, BL, and ARR did not indicate statistical significance between the experimental group and the control group. Conclusions The preservation of DF promotes soft tissue management in combined surgical and orthodontic treatment of labially impacted maxillary canine to achieve better periodontal status. Trial Registration Chinese Clinical Trial Registry ChiCTR2000029091, 2020-01-12.